How to be confident - Smith, James (HarperCollins publishers, 2022)
From two times number one Sunday Times bestselling author, James Smith, comes HOW TO BE CONFIDENT - the third instalment in James' no-nonsense guides to gaining the tools to empower your decision-making and change your life. Now, more than ever, we are so often lost within a cycle of negativity - from comparing ourselves to others and doom scrolling on social media, to a paralysis of choice and chasing external gratification that does nothing to nurture authentic happiness. We need confidence to master our true ambitions, realise our genuine strengths, and achieve the life we need, but might not know we want. Luckily, with his candid, no-nonsense advice, experience, and passion, James is here to lead the way.